Effectiveness of Teaching Materials to Support Merdeka Curriculum Learning on Basic Chemical Law Material on Learning Outcomes of Phase E SMA / MA - Ningsih, Rainy Setia; Mawardi , Mawardi (FKIP-Universitas Riau, 2024)
This study aims to determine the level of effectiveness of teaching materials to support merdeka curriculum learning on the material of the basic laws of chemistry on the learning outcomes of students. This research is a follow-up research from the Plomp model development research with a type of quasi-experimental research with a Nonequivalent control group design. This study consists of two samples, namely the experimental class and the control class with a total of 62 students selected by purposive sampling technique. Based on the results of the research conducted, the experimental class has an average N-gain value of 0.71 with a high category, and the control class with an average N-gain of 0.53 with a medium category. For hypothesis testing using the t-test, the t-count value is 5.323 and the t-table is 2.00. The results of data analysis show that learning by using teaching materials to support merdeka curriculum learning on basic laws of chemistry material effectively improves student learning outcomes.